Community perceptions to climate change in Finnish Lapland: Examining vulnerabilities and adaptive responses to the changing characteristics of Arctic tourism - Eva Kaján (Suomen matkailututkimuksen seura (Finnish Society for Tourism Research ), 2014)
-